(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Although Pinus sylvestris has a wide distribution throughout Europe, there are lack of scientifically approved information related to the sapwood timber strength parameters impregnated with natural resins comparing to the strenth parameters of non-resinous wood and industrially impregnated roundwood assortments using as the elements of wooden constructions such as wood poles for power lines. The main goal of the study is to work out the Pinus sylvestris stems which were previously treated using resin tapping technologies and harvested in final felling sites, timber strength parameters depending on timber quality characterized data based on the testing methods: moisture content - according to ISO13061-1:2014; density - according to ISO13061-2:2014; compression strength paralel to the grain- according to ISO 13061-17:2017; modulus of elasticity- according to ISO 13061- 4:2014; three point bending strength - according to ISO 13061- 3:2014. The results of the study might help for practical applications so that this wood specie can be processed more efficiently for the value - added products whose timber quality indicators would allow it to be used in wooden structures without additional chemical and thermal treatment, to establish more accurate quality requirements for roundwood assortments and to provide useful information for optimizing Scots pine harvesting management programs.